Logistics 4.0: Fundamentals and importance - Cabral Filho , Djalma Alves (Seven Editora, 2023)
The innovations of Logistics 4.0 are achieved with the implementation of characteristics that put the company ahead of competitors, through services that may have something practical or that simply have some item that identify them as a growing trend in Logistics for the coming years. With this information comes the following question: can one distinguish and choose, among the different logistics processes of Logistics 4.0, their fundamentals and trends, understanding their particularities, their uses and their strengths and weaknesses? The methodology applied to the work regarding the type of research was exploratory. As for the methods employed, it was bibliographic and documental. Regarding the data collection technique, the bibliographic research was applied. The data analysis technique was qualitative. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-071